2004
DOI: 10.1115/1.1797036
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of Gas Flow in Microchannels

Abstract: This paper presents an experimental investigation of laminar gas flow through microchannels. The independent variables: relative surface roughness, Knudsen number and Mach number were systematically varied to determine their influence on the friction factor. The microchannels were etched into silicon wafers, capped with glass, and have hydraulic diameters between 5 and 96 μm. The pressure was measured at seven locations along the channel length to determine local values of Knudsen number, Mach number and frict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
40
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(47 citation statements)
references
References 17 publications
6
40
1
Order By: Relevance
“…The agreement with the conventional theory was remarkable for the laminar regime, whereas in the turbulent case, the smaller the tube diameter was, the increasingly lower the values of the friction factor were than those predicted by the Blasius or the Filonenko correlations. The measurements by Lalonde et al [15] of air flow in a 52.8 µm microtube showed a good agreement with the predictions of the conventional theory, as did those of Turner et al [16], who investigated the laminar flow of nitrogen, helium and air for smooth and rough rectangular microchannels with hydraulic diameters ranging from 4 to 100 µm. Hsieh et al [17] investigated the behavior of nitrogen flow in a 24-mm long, 200-µm wide, and 50-µm deep microchannel for Reynolds numbers between 2.6 and 89.4 and a value of the Knudsen number ranging from 0.001 to 0.02.…”
Section: Introductionsupporting
confidence: 68%
“…The agreement with the conventional theory was remarkable for the laminar regime, whereas in the turbulent case, the smaller the tube diameter was, the increasingly lower the values of the friction factor were than those predicted by the Blasius or the Filonenko correlations. The measurements by Lalonde et al [15] of air flow in a 52.8 µm microtube showed a good agreement with the predictions of the conventional theory, as did those of Turner et al [16], who investigated the laminar flow of nitrogen, helium and air for smooth and rough rectangular microchannels with hydraulic diameters ranging from 4 to 100 µm. Hsieh et al [17] investigated the behavior of nitrogen flow in a 24-mm long, 200-µm wide, and 50-µm deep microchannel for Reynolds numbers between 2.6 and 89.4 and a value of the Knudsen number ranging from 0.001 to 0.02.…”
Section: Introductionsupporting
confidence: 68%
“…The results provide evidence for significant reduction in mass flow for rough surface channels both for helium and nitrogen. This result may appear contradicting to the conclusions of [8], but it may be explained by much larger (flatter) roughness angles used in [8] than that examined in this work. Although the impact of surface roughness at each given pressure is larger for helium than for nitrogen, it is similar if mass flow is plotted as a function of Knudsen number.…”
Section: Resultscontrasting
confidence: 55%
“…The related experimental studies of surface roughness are the work by Sugiyama et al [7] where triangular roughness in channel flows was studied numerically and experimentally for large Knudsen numbers and by Turner et al [8] where the surface roughness was found to have small effect on gas pressures inside a channel for several pressure ratios.…”
Section: Introductionmentioning
confidence: 99%
“…However to maintain an easy exchangeability of structures the design chosen was considered a good compromise. (5); outlet pressure measurement (6); mass flow meter (7); vacuum pump (8).…”
Section: Methodsmentioning
confidence: 99%
“…As the discontinuities first appear near the wall, it is clear that the gas-surface interactions play a major role in determining the flow behaviour in this region. Several experimental studies have been done to characterize gas flows in microchannels under slip flow (some examples can be found in the works proposed by Arkilic [7], Turner [8] and Pitakarnnop [9]). Yet, most of the produced results are based on the indirect evaluation of the rarefaction parameters with measurements performed outside the channels and do not offer a complete overview of the flow characteristics.…”
Section: Introductionmentioning
confidence: 99%